The transposable element Mdg3 in Drosophila melanogaster is flanked with the perfect direct and mismatched inverted repeats. - Bayev, A A (1980)
MDg3 is a family of mobile dispersed genetic elements represented by 15 copies in the haploid genome of D. melanogaster and flanked, like other similar elements, by the regions of homology. In the present work, these regions of mdg3 have been sequenced. The existence of perfect direct repeats 268 base pairs long has been demonstrated. Inverted repeats are located on the gene distal side of them. It is possible to construct a perfect 8 b.p. palindrome or a slightly mismatched 18 b.p. palindrome. The inverted repeats are flanked by two short 5 b.p. direct repeats.